Removal of Cationic Dye Methylene Blue Onto Moroccan Clay (Global Journal of Science Frontier Research, 2013)
This study reports the adsorption of Methylene Blue dye, a cationic dye used in dyeing cotton, wood and silk, on the crude and purified clay from Morocco. The adsorption experiments demonstrated that adsorption equilibrium is established after 20 minutes. Various experimental parameters were analyzed: adsorbent mass, initial dye concentration, adsorbent particle size. The experimental results showed that adsorption of Methylene Blue onto Moroccan Clay are related to the mass of the adsorbent and the initial dye concentration. The adsorption capacity was determined using the Langmuir and Freundlich isotherms. The adsorption kinetics of Methylene Blue was studied using the equations of the Firstorder and Second order reactions. The kinetics of adsorption of Methylene Blue dye onto Moroccan Clay can be described by a Second-order model. Results showed that the Moroccan clay can be considered as a good adsorbent for the removal of Methylene Blue and treatment of industrial wastewater.
Keywords: adsorption; moroccan clay; cationic dye; methylene blue; adsorption isotherms; kinetic models; industrial wastewater